2004
DOI: 10.1097/01.phm.0000140801.23135.09
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Effects of Whole-Body Vibration on Postural Control in Unilateral Chronic Stroke Patients

Abstract: The short-term effects of whole-body vibration as a novel method of somatosensory stimulation on postural control were investigated in 23 chronic stroke patients. While standing on a commercial platform, patients received 30-Hz oscillations at 3 mm of amplitude in the frontal plane. Balance was assessed four times at 45-min intervals with a dual-plate force platform, while quietly standing with the eyes opened and closed and while performing a voluntary weight-shifting task with visual feedback of center-of-pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
89
1
14

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(107 citation statements)
references
References 25 publications
3
89
1
14
Order By: Relevance
“…Among them, the vibration therapy has emerged over the last decades as a promising non-invasive treatment for osteoporosis. In fact -through a mechanism not yet univocally clarified -high-frequency vibratory stimulation is able to significantly stimulate osteogenesis in animal models (11)(12)(13)(14), and studies in human indicate that it improves bone mineral density (BMD), muscle strength and proprioception, particularly in people with osteoporosis or those with motor impairment from neuromuscular diseases of various etiologies (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30). The aim of this study is to evaluate the effect of combined treatment with focused mechano-acoustic vibration and pharmacological therapy on BMD and muscle strength in post-menopausal women.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, the vibration therapy has emerged over the last decades as a promising non-invasive treatment for osteoporosis. In fact -through a mechanism not yet univocally clarified -high-frequency vibratory stimulation is able to significantly stimulate osteogenesis in animal models (11)(12)(13)(14), and studies in human indicate that it improves bone mineral density (BMD), muscle strength and proprioception, particularly in people with osteoporosis or those with motor impairment from neuromuscular diseases of various etiologies (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30). The aim of this study is to evaluate the effect of combined treatment with focused mechano-acoustic vibration and pharmacological therapy on BMD and muscle strength in post-menopausal women.…”
Section: Introductionmentioning
confidence: 99%
“…2017; 8(1):e36793. 5 found that WBV training might improve balance and posture control of those who suffer from heart attack, Parkinson disease, and multiple sclerosis (18,41). In our previous study, we found that WBW training and creatine supplementation did not affect the static and dynamic balance in elder men in the short-term (42).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported beneficial effects of WBV in a variety of populations, for example, the elderly [9,[44][45][46] , untrained females [47,48] postmenopausal women [49,50] , Parkinson's disease [51][52][53] , multiple sclerosis [54] and stroke [55][56][57] .…”
Section: Discussionmentioning
confidence: 99%